Urgensi Manajemen Konflik dalam Meningkatkan Kinerja Sumber Daya Manusia di Lembaga Pendidikan Islam - Juliadarma, Minggusta; Yusuf, Ramli; Ilyas, Usman; Sebe, Kamarun M.; Kisman, Abida (Kartika: Jurnal Studi Keislaman, 2024)
Islamic educational institutions face complex challenges due to ongoing social, economic, and political changes, requiring continuous adaptation and quality improvement in educational services. Conflict management, therefore, is essential to ensure these institutions' sustainability and progress. This descriptive qualitative library research study deeply explores conflict and conflict management within Islamic educational institutions, using documentation for data collection and content analysis for data interpretation. Findings highlight the importance of integrating practical conflict management principles with Islamic values to foster communication, collaboration, and harmony, positively impacting productivity and the work environment. The study theoretically contributes to Islamic conflict management concepts and practically supports adaptive HR strategies. However, it remains limited in exploring diverse conflict management implementations across institutions with varying characteristics and the effectiveness of conflict models within different organizational cultures.